Serum biomarkers correlated with liver stiffness assessed in a multicenter study of pediatric cholestatic liver disease. Issue 2 (3rd February 2023) - Leung, Daniel H.; Devaraj, Sridevi; Goodrich, Nathan P.; Chen, Xinpu; Rajapakshe, Deepthi; Ye, Wen; Andreev, Victor; Minard, Charles G.; Guffey, Danielle; Molleston, Jean P.; Bass, Lee M.; Karpen, Saul J.; et al.
Abstract : Background and Aims: Detailed investigation of the biological pathways leading to hepatic fibrosis and identification of liver fibrosis biomarkers may facilitate early interventions for pediatric cholestasis. Approach and Results: A targeted enzyme‐linked immunosorbent assay–based panel of nine biomarkers (lysyl oxidase, tissue inhibitor matrix metalloproteinase (MMP) 1, connective tissue growth factor [CTGF], IL‐8, endoglin, periostin, Mac‐2–binding protein, MMP‐3, and MMP‐7) was examined in children with biliary atresia (BA; n = 187), alpha‐1 antitrypsin deficiency (A1AT; n = 78), and Alagille syndrome (ALGS; n = 65) and correlated with liver stiffness (LSM) and biochemical measures of liver disease. Median age and LSM were 9 years and 9.5 kPa. After adjusting for covariates, there were positive correlations among LSM and endoglin ( p = 0.04) and IL‐8 ( p < 0.001) and MMP‐7 ( p < 0.001) in participants with BA. The best prediction model for LSM in BA using clinical and lab measurements had an R 2 = 0.437; adding IL‐8 and MMP‐7 improved R 2 to 0.523 and 0.526 (both p < 0.0001). In participants with A1AT, CTGF and LSM were negatively correlated ( p = 0.004); adding CTGF to an LSM prediction model improved R 2 from 0.524 to 0.577 ( p = 0.0033). Biomarkers did not correlate with LSM in ALGS. A significant number of biomarker/lab correlations were found in participants with BA but not those with A1AT or ALGS. Conclusions: Endoglin, IL‐8, and MMP‐7 significantly correlate with increased LSM in children with BA, whereas CTGF inversely correlates with LSM in participants with A1AT; these biomarkers appear to enhance prediction of LSM beyond clinical tests. Future disease‐specific investigations of change in these biomarkers over time and as predictors of clinical outcomes will be important. Abstract :